Quality of parent–child interaction in underserved migrant areas in Kyrgyz Republic: a pilot study - Dahae Rim; Hyunsook Shin; Soonyoung Shon; Hyunhee Ma; Medina Muratbekova; Erlan Muratovich Akimbaev; Zamira Buzurmanovna Babalieva; Nuraiym Talapovna Djumaeva; Aijamal Ashimbekovna Tentieva (BMC Public Health, 2024)
Abstract Background After societal change in Kyrgyz Republic, the pattern of parent–child interaction in the changing parenting culture is an important factor influencing the positive development of Kyrgyz children. This study is aim to assess the quality of parent–child interactions in Kyrgyzstan by analyzing the interaction patterns and playfulness of children during free play at home. Methods This was a descriptive pilot study using video-recorded observations to explore parent–child interactions. The Dyadic Parent–Child Interaction Coding System and a playfulness instrument were used to assess the patterns and quality of the interaction. A total of 20 dyads of children aged 24 to 58 months and their parents, living in migrant communities of Kyrgyzstan, participated in this study. Results Major parent–child interaction patterns included 731 turns of parent–child dyads during 1040 episodes. Verbal as well as nonverbal behaviors of parents were observed while interacting with their children. Parents used direct and indirect commands most frequently, while praise was used the least in interactions. Children frequently used compliance as well as noncompliance when they interacted with their parents. Children had low playfulness scores while interacting with their parents. Cognitive spontaneity was the component with the lowest score among all subdomains of playfulness. Conclusion Future studies are recommended to develop strategies to facilitate parents’ active interaction with their children, promote children’s playfulness, and improve the quality of their mutual interaction.